EFEK MOTIVASI, GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA PADA KINERJA PEGAWAI - Dharmawan, K. Saha Aswina; Supartha, Wayan Gede; Piartini, Putu Saroyini (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.02.TAHUN 2017, 2017)
This study examines how work motivation, transformational leadership and work environment can affect on employee performance. This study take place in National Land Agency. Population is all employees of the National Land Agency in Bali with total sample of 100 employees selected from 9 regional unit across of Bali. Samples were selected using probability proportional and Linear Regression technique was used for analysis. The result proof that work motivation, transformational leadership and work environment have a positive and significant impact on performance. Hence, for the leaders at National Land Agency, it is recommended that they always do a variety of ways to keep the employee motivated so that employees can give their best performance. The leaders also need to describe their vision and mission more tangible. In addition, the leader also need to establish good work culture so that employees feel comfortable in working.
Keywords: Work motivation, transformational leadership, work environment, linear regression analysis